Design and Development of the “PETUALANGAN AKSA” Game as Javanese Alphabet Introduction Media - Rozan, Hanan Syafial; Padmasari, Ayung Candra; Nurhidayatulloh, Nurhidayatulloh (Universitas Pendidikan Indonesia (UPI), 2023)
Javanese script is one of the materials in Javanese language subjects that begin to be studied at the elementary school level. In SDIT Bina Insan Kamil Sidareja there are still many students who do not understand and have difficulty in learning Javanese characters. Factors that influence students' difficulties in learning Javanese characters are because students very rarely intersect with Javanese characters in everyday life. Teachers have not used learning media that can attract the attention of students. Overcoming these problems, researchers used the Luther-Sutopo version of the Multimedia Life Development Cycle (MDLC) development model in making the Aksa Adventure game as a medium for introducing Javanese script in Grade 4 SDIT Bina Insan Kamil Sidareja. The purpose of this study was to design the game